KEMAMPUAN MEMBACA PEMAHAMAN TEKS EKSPOSISI SISWA KELAS VII SMP BABUSSALAM PEKANBARU - Ika Apriyanti Ika Apriyanti; Dudung Burhanudin Dudung Burhanudin; Nursal Hakim Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT : this study discusses the ability of reading comprehension text Exposition grade VII SMP Babussalam Pekanbaru. As for the problems in this research is how the ability to read text understanding the exposition consists of four aspects, namely title, thesis, argument, and repeated the assertion. The methods used in this research is descriptive method quantitative research with samples as much as 41 students in grades VII SMP Babussalam Pekanbaru. The technique of collecting data in this study is to provide an objective test (multiple choice) to research samples, and then pass judgment in accordance with the results of the students' answers, and last, find the percentage for every aspect of reading comprehension text exposition as well as count. Based on research results, obtained summary that (1) the ability to specify the title of the category is with average 73,17, (2) ability to determine the low average category thesis 65,24, (3) the ability to determine the argument category low average 64,23, (4) the ability to determine an affirmation repeated low average 65,85 categories. Overall, the ability of reading comprehension text Exposition grade VII SMP Babussalam Pekanbaru category low with the average 67,12.Keywords: reading skills, understanding of the text of the exposition: